CALCULATION OF TWO-PHASE ZONE IN THE INTERVAL OF CRYSTALLIZATION OF ALUMINUM ALLOYS WITH USAGE OF THE THERMAL ANALYSIS - P. E. Lushchik; I. V. Rafalskij (Литьë и металлургия)
The new approach at calculation of two-phase zone in the interval of crystallization of aluminum-silicon alloys with use of thermal analysis is given.